Twist Effect on the Electronic and Transport Properties of 1D Helical Carbyne Chains. Issue 11 (24th September 2021) - Xu, Degao; Hou, Lu; Dong, Jiansheng; Hu, Huamin; Ouyang, Gang
Abstract : The electronic and transport properties of 1D helical carbyne chains (HCCs) are investigated in terms of continuum medium mechanics, density functional theory, and nonequilibrium Green's function by modeling a covalently sandwiched HCC connecting two zigzag graphene nanoribbon leads. It is found that the current of the device decreases by up to two orders of magnitude with increasing twisted pitch. The prodigious negative differential resistance (NDR) and rectifying effects are only exhibited in HCCs with multiple coil cycles. Moreover, graphene/HCC junctions with parallel/antiparallel magnetism configurations allow perfect (100%) spin polarization and NDR behaviors and simultaneously realize the switching effect during twisting. The results provide inspiration for the optimal design of nanomaterials and development of high‐performance multifunctional all‐carbon nanodevices. Abstract : Perfect dual‐spin filtering, negative differential resistance, and switching effects can be integrated in new kinds of functional devices based on 1D helical carbyne chains.